Short-chain fluorocarbon-based polymeric coating with excellent nonwetting ability against chemical warfare agents. Issue 13 (9th March 2022) - Jung, Hyunsook; Kwon, Jihyun; Jung, Heesoo; Cho, Kyeong Min; Yu, Seung Jung; Lee, Sang Myeon; Jeon, Mingyu; Im, Sung Gap
Abstract : A copolymeric coating containing short-chain fluorinated groups was synthesized and characterized to achieve excellent nonwetting ability against hazardous chemical warfare agents (CWAs). Abstract : The ongoing concerns and regulations on long-chain fluorinated compounds (C8 or higher) for nonwetting coatings have driven the market to search for sustainable alternative chemistries. In this study, a copolymeric coating containing short-chain fluorinated groups was synthesized to achieve excellent nonwetting ability against hazardous chemical warfare agents (CWAs). A copolymer of 1 H, 1 H, 2 H, 2 H -perfluorooctyl methacrylate (PFOMA) and ethylene glycol dimethacrylate (EGDMA, crosslinker) was directly coated onto a textile fabric via initiated chemical vapor deposition. The p(PFOMA- co -EGDMA) coating shows a rough-textured morphology with a bumpy, raspberry-like structure leading to high contact angles ( θ water > 150° and θ dodecane = 113.8°) and a small water shedding angle (<5°). Moreover, the p(PFOMA- co -EGDMA) coating was further analysed for application in military fabrics: air permeability, tensile strength, and safety against toxic perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS). Outstanding nonwetting was noticeably achieved against different CWAs, including bis(2-chloroethyl)sulfide (HD), pinacolyl methylfluorophosphonate (GD), and O -ethyl S -(2-diisopropylaminoethyl)methylphosphonothioate (VX) ( θ HD = 119.1°, θ GD = 117.0°, and θ VX = 104.1°). The coating retained its nano-structuration and nonwetting ability for water and n -dodecane despite being subjected to 250 cycles of Martindale abrasion and harsh chemicals (NaOH and HCl). The robustness and scalable straightforward preparation route of the coating make it an ideal approach for designing durable next-generation CWA nonwetting coatings for fabrics with favorable health and environmental properties.